Karakteristik Komputasi Penentuan Akar Kuadrat Bilangan Nonkuadrat Sempurna Beberapa Metode Iteratif Menggunakan Pemograman QBasic - Endaryono Endaryono (LPPM STKIP Kusuma Negara, 2020)
The completion of some mathematics problem not only used analytic methods but also by iterative processes through numerical methods. In numerical methods, besides students understood the calculation each iteration manually but also was necessary to understand the completion using coding or programming. QBasic is one program was easily downloaded. This paper discusses the determination of integer roots that are not perfect square numbers, namely a square root of 3 using numerical methods with iterative techniques. The purpose of writing is to look at computational characteristics in number iterations of Heron method, for two, false positions, and Newton Raphson. Research through simulations using QBasic promotion. The error value (error) in the simulation performed using the method is set at a value of 1x10-10 or iteration will still be if the error rate is more than the specified error value. The simulation results show that the error value of the square root of the number 3 ranges at 1.73205. The Heron method and the Newton Raphson method have the same number of iterations, which are 6 iterations, relatively less than other iterative methods. The conclusion of the research is the determination of the root of the citrate from the number 3 Heron method and Newton Raphson method provide a better computational performance of the number of iterations than the method for two and the false position.